International Community Engagement: Transfer Edukasi Agribisnis Terhadap Pelajar Indonesia di Malaysia - Akbar Ali Arbai; Ertika Fitri Lisnanti; Heru Setyadi; Eerlin Widya Fatmawati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: The increasing number of Indonesian students studying abroad, particularly in Malaysia, demands strengthening knowledge capacity from an early age to compete globally, including in the agribusiness sector. However, observations indicate that Indonesian students in Malaysia still have a limited understanding of basic agribusiness concepts. This international community service activity aims to improve basic agribusiness understanding through educational transfer through visual media. Method: The implementation method includes a preparation stage, direct learning implementation supported by visual video media, and evaluation using pre-test and post-test instruments. This activity involved 15 elementary school students in grades 4-5, aged 10-12 years, at a learning center in Kuala Lumpur, Malaysia. Results: The results showed an increase in participants' average score from 50% on the pre-test to 81.25% on the post-test, a 31.25% increase. These findings indicate that the use of visual video media is effective in improving students' understanding of basic agribusiness concepts. Conclusion: This community service activity supports the transfer of agribusiness education to Indonesian students abroad and strengthens the implementation of the three pillars of higher education in the context of community service.